Perlawanan Pers Islam pada Masa Orde Baru - Abdul Firman Ashaf (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2006)
This study discussed Republika—a widely circulated national newspaper in Indonesia—as ICMI’s articulation medium. The main question lies here is how did Republika conducted its social practices role in the New Order Era in order to frame Islam and its state relation? Employing descriptive qualitative method, this research analyzed some news event dated back on July, 26th, 1996. The research aimed to understand ICMI political journalism reflected by Republika daily news, and relate it to the journalist respons and sociopolitical context during New Order Era. It was found that Republika was an actor resulted from sociopolitical struggles during New Order Era. At the end of 90’s, Republika was really aware of the objective conditions happened during New Order era. Republika was also understanding such changes that happened within elites and society, and then placed itself as the actor of change by conducting a kind of resistance through its respons and report. As an alternative discourse, this resistance was appeared on Republika’s report concerning the involvement of Partai Rakyat Demokratik (PRD—Democratic People Party) in July, 27th, 1996 chaos.